Vanguardia política y vanguardia artística en las revistas de Vicente Huidobro. El discurso polémico en Ombligo y Vital (1934, 1935) - Ibarlucía, Rocío (2020)
The journals Ombligo and Vital led by Vicente Huidobro between 1934 and 1935 present a repertoire of discourses of the Russian Revolution, the workers' movement in the US and Chilean conservative policies that lead to redefine its figure of poet, usually typecast in the artistic side of the Latin American vanguards. This article evaluates the debates between Huidobro and other Chilean intellectuals, poets, literary critics and political leaders gathered in these publications. After analyzing the controversial speech from argumentation theory (Perelman, 1989), we observe a ridicule of rhetorical argumentation policy through ironic commentaries that never fail to denounce the doctrines of right. These organs of diffusion, then build a sustained write in the irony in order to contest a privileged place in the literary field, forcing the own Huidobro to review his project and, consequently, to restore the loans between aesthetics and political vanguards.